Impact of individual components of emergency department pediatric readiness on pediatric mortality in US trauma centers. Issue 3 (1st March 2023) - Remick, Katherine; Smith, McKenna; Newgard, Craig D.; Lin, Amber; Hewes, Hilary; Jensen, Aaron R.; Glass, Nina; Ford, Rachel; Ames, Stefanie; Cook, Jenny; Malveau, Susan; Dai, Mengtao; et al.
Abstract : This study of 555 US trauma centers demonstrated lower mortality risk among injured children is associated with presence of a validated pediatric triage tool, a comprehensive quality improvement process, and presence of nurse and physician pediatric emergency care coordinators. Abstract : BACKGROUND: Injured children initially treated at trauma centers with high emergency department (ED) pediatric readiness have improved survival. Centers with limited resources may not be able to address all pediatric readiness deficiencies, and there currently is no evidence-based guidance for prioritizing different components of readiness. The objective of this study was to identify individual components of ED pediatric readiness associated with better-than-expected survival in US trauma centers to aid in the allocation of resources targeted at improving pediatric readiness. METHODS: This cohort study of US trauma centers used the National Trauma Data Bank (2012–2017) matched to the 2013 National Pediatric Readiness Project assessment. Adult and pediatric centers treating at least 50 injured children (younger than 18 years) and recording at least one death during the 6-year study period were included. Using a standardized risk-adjustment model for trauma, we calculated the observed-to-expected mortality ratio for each trauma center. We used bivariate analyses and multivariable linear regression to assess for associations between individual components of ED pediatric readiness and better-than-expected survival. RESULTS: Among 555 trauma centers, the observed-to-expected mortality ratios ranged from 0.07 to 4.17 (interquartile range, 0.93–1.14). Unadjusted analyses of 23 components of ED pediatric readiness showed that trauma centers with better-than-expected survival were more likely to have a validated pediatric triage tool, comprehensive quality improvement processes, a pediatric-specific disaster plan, and critical airway and resuscitation equipment (all p < 0.03). The multivariable analysis demonstrated that trauma centers with both a physician and a nurse pediatric emergency care coordinator had better-than-expected survival, but this association weakened after accounting for trauma center level. Child maltreatment policies were associated with lower-than-expected survival, particularly in Levels III to V trauma centers. CONCLUSION: Specific components of ED pediatric readiness were associated with pediatric survival among US trauma centers. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :